2015
DOI: 10.1177/1948550615598376
|View full text |Cite
|
Sign up to set email alerts
|

Stigma-Based Rejection and the Detection of Signs of Acceptance

Abstract: After people experience social rejection, one tactic to restore a sense of belonging is to selectively attend to and readily perceive cues that connote acceptance. The multimotive model of responses to rejection suggests that contextual features of the rejection are important determinants of how people are motivated to respond. According to this model, when rejection is construed as pervasive and chronic, people will be less likely to adopt strategies that promote belonging. Across two studies, we found that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Other studies have found an opposite pattern of results reporting that excluded participants viewed social stimuli particularly negatively, instead. Excluded participants, compared to control groups, rated ambiguous actions as more hostile (DeWall, Twenge, et al ., , Experiments 2–4), were slower to judge faces as happy when the expression turned from neutral to a smile (Smart Richman et al ., ), and were biased to view others as portraying averted gaze (Syrjämäki, Lyyra, & Hietanen, ).…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have found an opposite pattern of results reporting that excluded participants viewed social stimuli particularly negatively, instead. Excluded participants, compared to control groups, rated ambiguous actions as more hostile (DeWall, Twenge, et al ., , Experiments 2–4), were slower to judge faces as happy when the expression turned from neutral to a smile (Smart Richman et al ., ), and were biased to view others as portraying averted gaze (Syrjämäki, Lyyra, & Hietanen, ).…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 99%
“…Theoretical models that describe the effects of exclusion on motivation (Smart Richman & Leary, ; Williams, ) might therefore offer a useful framework for understanding why excluded individuals sometimes judge social stimuli as positive and affiliative (Maner et al ., ), and sometimes as exclusive and threatening (DeWall, Twenge, et al ., ). To thoroughly understand this issue, future research should carefully investigate how different situational factors (Syrjämäki et al ., ), individual traits (Smart Richman et al ., ), and characteristics of the target stimuli (Brown, Sacco, & Medlin, ) moderate the effects of exclusion on judgements.…”
Section: How Does Exclusion Modulate Social Information Processing?mentioning
confidence: 99%
See 1 more Smart Citation
“…Rejection is often described as a form of social exclusion, primarily characterized by direct negative attention, suggesting one is not wanted (and this is different from ostracism, primarily characterized by the experience of being ignored; Riva & Eck, 2016). Minority groups often experience social rejection via discrimination and stigmatization (Branscombe et al, 1999; Smart Richman & Leary, 2009; Smart Richman, Martin, & Guadagno, 2016) and when rejection persists over time, its effects can be detrimental for individuals' health and well‐being (Bernstein, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some theorists also argue that other types of negative social experiences can involve being socially excluded, such as discrimination and stigmatization (Goffman, 1963;Kerr & Levine, 2008;Kurzban & Leary, 2001;Richman, Martin, & Guadagno, 2016).…”
Section: Social Exclusionmentioning
confidence: 99%